India's Journey with Corporate Social Responsibility-What Next? - Majumdar, Arjya B. (Journal of Law and Commerce, 2015)
One of the causes for raised eyebrows to the Companies Act, 2013 is Section 135. The provision mandates companies meeting certain requirements to compulsorily contribute to corporate social responsibility (CSR) activities, or explain the failure to do so. While this has been the subject of an ongoing debate ever since the provision was suggested in 2009, the provision in question has been met with considerable resistance from the industry. Arguments against Section 135 range from specific critiques of the semantics of the statute to critiques of the failure of India as a welfare state altogether. What this paper seeks is to attempt a definitive outline of the CSR law and practice in India, its roots in Hinduism, Buddhism and Islam, Gandhian philosophies and the pre-2013 position on CSR. It shall also attempt to provide a critical analysis of Section 135 of the Companies Act, 2013 and how the provision may be ignored, or worse—misused. Three arguments are presented in this regard. Firstly, that Section 135 constitutes a departure from the accepted position that CSR needs to be imbibed into the business and management principles of a company and is heading towards a potentially destructive conversion of the principles of CSR into corporate altruism. Secondly, the provisions of Section 135 make the Board of Directors liable to show to their shareholders—the compliance of the company’s social responsibilities. Instead, if the company is to have and comply with social responsibilities, the same should be ascertained by the society, or at least a representative of society. Finally, there is a slew of extant laws in India which also mandate certain companies to take into account their social responsibilities.